Sprawność językowa dzieci z uszkodzonym narządem słuchu - Bieńkowska, Katarzyna (Teoria i praktyka logopedyczna. Wybrane zagadnienia, 2018)
The following paper presents the results of a language test for hearing impaired children. Author’s original research tools were used and 159 children from all over Poland of age ranging from 6 and half to 8 years were examined. Speech understanding and speaking abilities were diagnosed. Alternative methods of communication have also been considered. The Author determined what internal and external factors affect the language skills of hearing impaired children.